Determination of amino acid composition of foods by photometric methods, part 2 - determination of methionine, cystine, lysine and arginine - Kiss, Dóra; Juhászné Tóth, Réka; Zurbó, Zsófia; Csapó, János (Élelmiszervizsgálati Közlemények, 2020)
In the second part of our review paper on the photometric determination of the amino acid content of foods, methods of determination of two essential amino acids (methionine, lysine) and two semi-essential amino acids (cystine, arginine) reported in the literature are described. Selective determination of the two sulfur-containing amino acids is made possible by the fact that both the methylmercapto group of methionine and the sulfhydryl group of cysteine formed by the reduction of cystine can be subjected to specific derivatization reactions which are characteristic of only these amino acids. The same can be said for the ε-amino group of lysine and the guanidine group of arginine, which allow the specific determination of the amino acids in question with the help of special colour reactions. The reaction most suitable for the determination of methionine is one in which the discolouration of platinum and palladium complexes is catalyzed by methionine, and from which the amount of methionine can be deduced. Under appropriate conditions, organic sulfides and cystine do not interfere with the reaction. The first step in the determination of cystine and cysteine is the reduction of cystine to cysteine, followed by a reaction between cysteine and a derivatizing agent, most commonly 5,5’-dithiobis(2-nitrobenzoic acid). Quantification can be performed by the photometric measurement of the coloured compound formed. In the case of lysine, the free ε-amino group of lysine is reacted with the derivatizing agent, most commonly 1-fluoro-2,4-dinitrobenzene, and then colour intensity is measured. In the case of arginine, most often the reaction between the guanidine group, α-naphthol and sodium hypobromide serves as the basis for the determination.